ANTI-STRESS BAG FOR MEDICAL STAFF (NURSE), THE IMPORTANCE OF AN ANTI-STRESS BAG ADAPTED TO WORK ACTIVITY, STRESS REDUCTION, MAINTAINING EMOTIONAL STABILITY, AND INCREASING WORK ABILITY (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
In the context of the COVID-19 pandemic, medical employees—especially nurses—faced unprecedented workloads, emotional exhaustion, and chronic stress. These conditions negatively affected their work quality, communication, and decision-making abilities. Therefore, there is a growing need for practical, portable, and effective tools that provide immediate relief from psychological and physical strain during work.